PENGARUH PENERAPAN JOYFUL LEARNING TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI BANGUN DATAR KELAS III SDN 001 TERATAK - Bayu Saputra; Fadhilaturrahmi; Zulhendri; Joni; Rusdial Marta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the implementation of the joyful learning strategy on the mathematical problem-solving ability of the third-grade students of SDN 001 Teratak on plane geometry. This study uses a quantitative approach with a pre-experimental design method using a one-group pretest-posttest design. The subjects of the study were the third-grade students of SDN 001 Teratak, consisting of 20 students in the experimental class and 20 students in the control class. Data collection techniques were carried out through mathematical problem-solving ability tests in the form of pretests and posttests as well as observations during the learning process. The research instrument was a validated test item. Data were analyzed using descriptive statistics and inferential statistics with normality tests and independent sample t-tests assisted by SPSS. The results showed that based on the independent sample t-test, the significance value was smaller than 0.05 (Sig. <0.05), so there was a significant difference in conceptual understanding between students who learned using the joyful learning strategy and students who learned with the CTL method. Thus, the use of joyful learning strategies has a significant effect on increasing students' conceptual understanding compared to CTL learning on students' mathematical problem-solving abilities on flat shape material for class III SDN 001 Teratak.